2011
DOI: 10.3389/fpsyt.2011.00001
|View full text |Cite
|
Sign up to set email alerts
|

Impulse Control Disorders: Updated Review of Clinical Characteristics and Pharmacological Management

Abstract: Impulse control disorders (ICDs) are characterized by urges and behaviors that are excessive and/or harmful to oneself or others and cause significant impairment in social and occupational functioning, as well as legal and financial difficulties. ICDs are relatively common psychiatric conditions, yet are poorly understood by the general public, clinicians, and individuals struggling with the disorder. Although ICD treatment research is limited, studies have shown ICDs may respond well to pharmacological treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 83 publications
5
103
0
4
Order By: Relevance
“…In contrast, research indicates that urges to pull hair in trichotillomania are precipitated not by obsessional fears, but rather by feelings of general tension, depression, anger, boredom, frustration, indecision, or fatigue (Christenson et al 1993). Studies also suggest that hair pulling in trichotillomania leads to pleasurable feelings (Grant & Potenza 2004, Schreiber et al 2011), a phenomenon not observed with rituals in OCD (Stanley et al 1992).…”
Section: Wwwannualreviewsorg • Obsessive-compulsive and Related Dismentioning
confidence: 87%
“…In contrast, research indicates that urges to pull hair in trichotillomania are precipitated not by obsessional fears, but rather by feelings of general tension, depression, anger, boredom, frustration, indecision, or fatigue (Christenson et al 1993). Studies also suggest that hair pulling in trichotillomania leads to pleasurable feelings (Grant & Potenza 2004, Schreiber et al 2011), a phenomenon not observed with rituals in OCD (Stanley et al 1992).…”
Section: Wwwannualreviewsorg • Obsessive-compulsive and Related Dismentioning
confidence: 87%
“…Clinical improvements were associated with higher baseline connectivity between the DLPFC, sgACC, and other areas of the mPFC. Others have reported associations between baseline mPFC connectivity and response to psychopharmacological antidepressants (75, 76). Together, these results suggest that rs-fMRI scans obtained prior to treatment have the potential for applications in predicting treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…They consist in compulsive and repetitive behaviours that are excessive and/or eventually harmful to oneself or others1 and include compulsive gambling, sexual behaviour, buying and eating, as well as punding, excessive hobbyism and overuse of dopamine agents, known as dopamine dysregulation syndrome (DDS) 2. The estimated prevalence of ICDs in PD is about 14%3 or higher according to other reports 4.…”
Section: Introductionmentioning
confidence: 99%